Evolution of the occurrence of Tityus serrulatus (LUTZ & MELLO, 1992) in the state of Santa Catarina - Taciana Mara da Silva Seemann; Ana Paula da Rocha; Fabíola Cremonese; Marisete Canello Resener; Andrea Petry; Ana Carolina Conchon Costa (Revista da Sociedade Brasileira de Medicina Tropical, 2023)
ABSTRACT Background: Scorpions are a leading cause of envenomation in Brazil. The species Tityus serrulatus is associated with the most severe cases, especially in children. Despite not being endemic to the state of Santa Catarina, such occurrences have increased more than 500% in the state recently. Therefore, this study aimed to analyze the occurrence of envenomation by T. serrulatus, attended by the Center for Toxicological Information and Assistance of Santa Catarina. Methods: This was a retrospective and descriptive study of the occurrence of T. serrulatus, identified by the agency, from 2014 to 2021 in Santa Catarina, using data obtained by the BI-DATATOX system. Results: A total of 112 occurrences were classified as envenomation. Of these cases, 48.2% were recorded in the Itajaí Valley region and 33% in Greater Florianópolis. Men were involved in 59.8% of these, and the most common age group was 20-39 years (39.3%). Most envenomation occurred in urban areas (89.3%) under non-occupational circumstances (83%). Stings were more frequent on the hands (50.9%). Care was sought within 1 h after the event in 75.9% of the cases, and 94.6% were classified as mild. Conclusions: Occurrence of envenomation involving T. serrulatus in Santa Catarina increased significantly during the study period. Most cases occurred in urbanized areas, which suggests that they might have been transported from other states, and it must be considered that, in the urban environment, scorpions find a large supply of food and shelter and a reduced number of specific predators, allied to parthenogenesis.